Cognitive fusion and personality traits in the context of mindfulness: A cross-sectional study - Pux, Sarah; Hahn, Eric; Bergmann, Niklas; Hahne, Inge; Pauly, Luca; Ta, Thi Minh Tam; Pijenborg, Gerdina H. M.; Böge, Kerem (PLOS ONE, 2022)
Objectives Meditation and mindfulness, though rooted in eastern traditions, have been increasingly embraced in western psychology. However, questions remain regarding the mechanisms through which the beneficial effects of mindfulness occur. The present study aimed to address cognitive fusion as a potential mediator between mindfulness and negative affect and whether the mindfulness-cognitive fusion link is moderated by personality factors in an international sample of frequent meditators. Methods An international sample of 739 frequent meditators completed measures of mindfulness (Southampton Mindfulness Questionnaire), cognitive fusion (Cognitive Fusion Questionnaire), negative affect (Brief Symptom Checklist), and personality (Big Five Inventory) in an online survey. Using SPSS Process Macro, cognitive fusion was examined as a mediator between mindfulness and negative affect. Furthermore, Extraversion, Conscientiousness, and Neuroticism were investigated as moderators in the mediation model. Results Cognitive fusion was found to be a partial mediator between mindfulness and negative affect (b = -0.249; 95% CI, [-0.289, -0.203]), whereas the examined personality factors were not found to moderate the present model (E: t(734) = 0.951, p = .342); C: t(734) = -0.042, p = .967; N: t(734) = -2.271, p = .023). Conclusions This study suggests that cognitive fusion plays a significant role in the association between mindfulness and negative affect. These findings indicate the importance of how individuals internally respond and relate to experiences and the instrumental value of mindfulness effects beyond and outside of mindfulness-based interventions.